Air-sea interaction on a seasonal scale over north Indian Ocean-Part I: Inter-annual variations of sea surface temperature and Indian summer monsoon rainfall - JOSEPH, P. V.; PILLAI, P. V. (MAUSAM, 1984)
Monthly mean sea surface temperature (SST) obtained from ship observations have been studied for two 'selected representative areas' (SRA) in the Arabian Sea and one in the Bay of Bengal for the 13-year period 1961 to 1973. Each SRA is 3 degrees longitude X 2 degrees latitude. They are centred, A at 11 deg, 00’N, 59 deg. 30'E, Bat 14 deg. 00'N, 71 deg. 30'E and C at 11 deg. 00' N, 83 deg. 30' E. 12 monthly running means of the monthly mean SST of each SRA shows a pronounced three-year oscillation, during the whole period. The series of monthly anomalies of SST for A, Band C were subjected to harmonic an power spectrum analyses, which also show a apart, from the annual variation, the only prominent periodicity is the 3-year variation. For the 9-year period 1965 to 1973, five-degree square averages of monthly mean SST have been worked out for the Indian. Ocean area north to 15 deg. S. It is found that the 3-year oscillation in SST covers a large area of north Indian Ocean, where power spectrum analysis of SST monthly anomalies shows significant peaks at confidence level 95% for this oscillation. Correlations between monsoon rainfall of India and the SST anomalies at A, Band C have been worked out using data of 1961 to 1973. It is found that the SST of pre-monsoon months is positively correlated with the following monsoon rainfall, but the correlation is low and not statistically significant. However, the monsoon rainfall is significantly negatively correlated with the post-monsoon SST of areas A, Band C.